(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The roman attack against the celtiberian city of Segeda I (Mara, Zaragoza) is referred in classical texts that provide the date of 153 BCE. This date is proved by ante quem datations offered by archaeological excavations. There are several evidences that show Hellenistic influences: in the ways of wine consumption, in the capacity measures of the kalathoi, in the plan of the “strigil house” —where one of this instruments was recovered— and in the “Sun sanctuary” with its astronomical observatory related to the lunisolar At- tic calendar corresponding the Metonic cycle.